Design of Self-Storage and Tremella-like MoS2 Lubricant Induced by Laser Irradiation for Achieving Stable Ultralow Friction in Atmosphere - Dong, Yifan (Langmuir : the ACS journal of surfaces and colloids, 2025)
Molybdenum disulfide (MoS2) has a typical layered structure and is widely used in the lubrication field. However, its nanosheets are difficult to disperse and prone to agglomeration in lubricating oil, which makes it challenging to achieve ultralow friction in the atmospheric environment and restricts its practical applications. Therefore, it is of great significance to solve the disperse and agglomeration problems of MoS2 to realize ultralow friction. In this paper, MoS2 nanosheets synthesized by the hydrothermal method were taken as the target material, and tremella-like MoS2 nanospheres were successfully prepared by laser irradiation in liquid. This technique realizes the reshaping of the morphology of MoS2 under normal temperature and pressure and is simple, clean, and efficient. Importantly, these unique tremella-like nanospheres, as additives for glycerol, can not only effectively inhibit the aggregation of nanomaterials, possessing excellent dispersion stability and good wetting properties, but also significantly reduce the friction and the wear rate, enabling the system to achieve long-term stability and ultralow friction in the atmospheric environment. The analysis of the worn surfaces indicates that the effective formation of the MoS2 tribofilm and its self-storage lubrication characteristics are the key factors for achieving ultralow friction. This research promotes the application of ultralow friction materials in the engineering field and provides a theoretical basis for the development of new lubricants